CASE STUDY OF THE IMPLEMENTATION OF THE MICRO, SMALL, AND MEDIUM ENTERPRISE HOME INDUSTRY PROGRAM IN NENAS SIAM VILLAGE, MEDANG DERAS DISTRICT, BATU BARA REGENCY - Sri Devi; Jhon Simon; Fandi Alfiansyah Siregar (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
This study aims to analyse the implementation of the Micro, Small, and Medium Enterprises (MSMEs/UMKM) home-industry programme in Nenas Siam Village, Medang Deras Sub-district, Batu Bara Regency. Home-industry MSMEs play a strategic role in the economic empowerment of rural communities, particularly in raising household income and creating family-based employment opportunities. However, the implementation of MSME programmes at the village level still faces multiple challenges, ranging from capital, human resource capacity, and marketing to institutional aspects. The study uses a descriptive qualitative approach with a case-study method. Data were collected through in depth interviews, observation, and documentation involving home-industry MSME actors, village officials, programme facilitators, and other related stakeholders. Data were analysed using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The findings show that the implementation of the home-industry MSME programme in Nenas Siam Village has progressed through socialisation, training, mentoring, and business facilitation. Nevertheless, programme implementation has not been fully optimal. The village government plays a role as facilitator and connector among parties, while related agencies and facilitators provide technical and managerial support. The main constraints faced by businesses include limited capital, equipment, marketing, and low business management capacity. Despite these constraints, the programme has produced positive impacts in terms of higher product quality, increased self-confidence among entrepreneurs, and contribution to household income. The study provides recommendations for governments and stakeholders to strengthen the implementation of home-industry MSME programmes in rural areas. Keywords: MSME; Home Industry; Community Empowerment; Case Study; Village